Improvement of STEAP 1 Biosynthesis from Pichia pastoris X33 cells under an optimized feeding strategy - Duarte, Diana Rute Tavares (2017)
Prostate cancer (PCa) is the most common type of cancer in aged men. Actually, the main problem arises from the fact that both PCa diagnosis and therapy are still invasive and limited in advanced stages of this disease. Thus, it is necessary to identify, study and characterize specific proteins whose expression correlates with these pathologies. Concerning this, it has been suggested that the Six-transmembrane epithelial antigen of the prostate 1 (STEAP1) protein as a good biomarker and/or immunotherapeutic target for PCa. It is located in the plasma membrane of epithelial cells, in both tight and gap junctions. STEAP1 is composed of six transmembrane domains, connected by three extracellular and two intracellular loops. Therefore, it has been suggested that this protein plays an important role in intracellular communication between cancer cells, contributing to the cancer process and tumor invasiveness. The characterization of STEAP1 structure and function might allow the development of specific inhibitors, envisaging a decrease of its oncogenic role. However, the techniques used for protein structural and functional characterization demand for high quantities of the target protein, which may be achieved through the recombinant DNA technology. Therefore, the aim of this work was to improve STEAP1 biosynthesis from mini-bioreactor Pichia pastoris X33 methanol induced cultures. This was achieved through the study of different glycerol and methanol feeding profiles during the fed-batch phases. Briefly, the medium supplementation with Proline 1M in a gradient glycerol and constant methanol feed, leads to high quantities of STEAP1 (increase for the double). An exponential glycerol and constant methanol feed produces fewer amounts of the protein but in the correct molecular weight (~35kDa). The influence of the fermentation conditions on STEAP1 molecular weight and N-glycosylation was studied using the enzyme PNGase F. The results showed that a constant glycerol feed seems to produce STEAP1 with N-glycosylation. However, the dimers produced in the gradient glycerol feed are not due N-glycosylation process. Two-dimensional electrophoresis proves this, and it was demonstrated that they correspond to different N-glycosylation patterns. Overall, it was successfully optimized a new strategy for recombinant STEAP1 biosynthesis, through the study of different feeding profiles. Future work encompassing will be developed an alternative strategy to perform the purification on the target protein.